Comparison of Enzyme-Immunoassay and Rapid Immunochromatography Test for Detecting Helicobacter pylori Stool Antigen - Prasetyo, Dwi; H. J, Gerritsen; P., Mertens; V., Labrune; T, Leclipteux; E. J, Kuijper (Majalah Kedokteran Bandung, 2014)
The rapid immunochromatography for Helicobacter pylori stool antigen (HpSA) test is a recently developed method for detection of Heicobacter pylori (H. pylori)  infection. The objective of this study was to compare rapid HpSA test with a conventional enzyme-immunoassay (EIA) and to determine the prevalence of H. pylori infection in symptomatic (recurrent abdominal pain/RAP) Indonesian children. One hundred and two high school children aged 12–18 years old in Bandung with RAP from July to November 2008 were enrolled, excluding children who had additional symptoms, such as diarrhea or fever. First study was performed in 102 samples in laboratory of Leiden University Medical Center (LUMC), Helicobacter pylori infection was detected by a conventional EIA and rapid test. A second study was performed on a stored collection of 32 feces samples previously tested positive for H. pylori by EIA in laboratory of LUMC; these samples were retested by both assays. The results showed the sensitivity, specificity, positive predictive value, and negative predictive value of the rapid test were 100%, 98.2%, accuracy 98.5%, 92.6% and 100%, respectively, from 134 tested samples. The overall prevalence of H. pylori infection among Indonesian children was 3% by EIA at first testing. In conclusion, the prevalence of H. pylori infection among symptomatic Indonesian children is very low and the new developed Pylori-Strip test shows good performance, very fast, and easy to use compared to EIA.  [MKB. 2014;46(1):52–6]Key words: Children, diagnostic, Helicobacter pylori, immunochromatographyPerbandingan Pemeriksaan Enzyme-Immunoassay dan Rapid Immunchromatography untuk Mendeteksi Helicobacter pylori Stool AntigenPemeriksaan Helicobacter pylori stool antigen (HpSA) menggunakan rapid immunochromatography (rapid HpSA) merupakan metode yang saat ini sedang berkembang untuk mendeteksi infeksi H. pylori. Tujuan penelitian ini untuk membandingkan metode rapid HpSA dengan metode konvensional yaitu enzyme-immunoassay (EIA) dan menentukan prevalensi infeksi H. pylori pada anak dengan gejala sakit perut berulang (SPB) di Indonesia. Sebanyak 102 anak sekolah menengah usia 12–18 tahun di Bandung dengan keluhan SPB ikut dalam penelitian ini, dilaksanakan dari Juli–November 2008. Anak dengan gejala tambahan, seperti diare dan demam, dikeluarkan dari penelitian. Penelitian pertama dilakukan pada sampel feses 102 anak di laboratorium Leiden University Medical Center (LUMC), Helicobacter pylori terdeteksi baik dengan pemeriksaan EIA konvensional maupun rapid test. Penelitian kedua dilakukan pada 32 buah sampel feses simpanan di laboratorium LUMC yang sebelumnya menunjukkan hasil positif dengan pemeriksaan EIA, sampel ini juga diperiksa menggunakan kedua metode. Hasil penelitian menunjukkan sensitifitas, spesifisitas, akurasi, positive predictive value, dan negative predictive value, dengan hasil 100%, 98,2%, 98,5%, 92,6%, dan 100% dari 134 sampel yang diuji. Prevalensi infeksi H. pylori pada anak Indonesia dengan keluhan SPB sekitar 3% pada pemeriksaan pertama. Simpulan, prevalensi infeksi H. pylori pada anak SPB di Indonesia sangat sedikit dan pemeriksaan Pylori-strip (rapid test) merupakan pemeriksaan yang sangat baik dan cepat serta mudah digunakan dibandingkan dengan EIA. [MKB. 2014;46(1):52–6]Kata kunci: Anak, diagnosis, Helicobacter pylori, immunochromatographyDOI: 10.15395/mkb.v46n1.228